Ultrasonic-assisted extraction to enhance the recovery of bioactive phenolic compounds from Commiphora gileadensis leaves - Aiman Awadh Saleh, Mokaizh; Nour, Abdurahman Hamid; Kerboua, Kaouther (Elsevier B.V., 2024)
The “ultrasonic-assisted extraction (UAE)” method was utilized in this work to assess how different process parameters affected the yield and recovery of phenolic compounds from the leaf of Commiphora gileadensis, which is one of the medicinal plants with a variety of biological functions. Its leaf is used for a various of therapeutic applications, such as the treatment of bacterial infections, inflammation, and wound healing. The “One-Factor-At-a-Time (OFAT)” approach was employed to examine the impacts of various UAE process parameters on the process of extraction, which include time of extraction, sample/solvent ratio, ultrasonic frequency, and solvent (ethanol) concentration. The extracts were then investigated for the presence of several phytochemicals using analytical techniques such as “Gas Chromatography-Mass Spectroscopy (GC–MS)” and “Fourier Transform Infrared Spectroscopy (FTIR)” studies. The findings showed that the maximum extraction yield, the total phenolic content (TPC), and the total flavonoids content (TFC) of the ethanolic extract of the leaves of C. gileadensis using the UAE method were at 31.80 ± 0.41 %, 96.55 ± 2.81 mg GAE/g d.w. and 31.66 ± 2.01 mg QE/g d.w. accordingly under a procedure duration of 15 min, ultrasonic frequency of 20 kHz, solvent/sample ratio of 1:20 g/mL, and solvent concentration of 40 % v/v. The leaves extract of C. gileadensis included 25 phenolic compounds that were previously unreported, and GC–MS analysis confirmed their presence. Hence, it follows that the UAE technique can successfully extract the phytochemicals from C. gileadensis for a variety of therapeutic uses.